From Single to Multi-document Summarization: A Prototype System and its Evaluation - Lin, Chin-Yew; Hovy, E.H. (The 40th Annual Meeting of the Association for Computational Linguistics (ACL'02), 2002)
NeATS is a multi-document summarization system that attempts to extract relevant or interesting portions from a set of documents about some topic and present them in coherent order. NeATS is among the best performers in the large scale summarization evaluation DUC 2001.